Infecção em Pacientes Neutropênicos: AvaIiação Retrospectiva de Fatores de Risco e da Eficácia Terapêutica - Velasco, Eduardo D. (2023)
In order to try to evaluate risk factors during infection episodes in neutropeunic patients, a retrospective study was performed in 209 medical records of patients, admitted to the Instituto Nacional de Câncer, during a period of 36 months, who had 317 febrile episodes. Several factors, such as degree of neutropenia, bacteremia, lung infiltrates and severe thrombocytopenia (<30.000/ mm3) did influence the clinical evolution of the infections process. An univariate analysis demonstrated a higher mortality rate for those patients. Patients severely neutropenic (less than 100/m3) had significant higher incidence of the studied risk factors. There was an important correlation between the severity of neutropenia and the presence of bacteremia, lung infiltrates and severe thrombocytopenia. Patients who developed bacteremia or thrombocytopenia had a higher incidence of lung infiltrates and, consequently, a higher mortality rate. There was no statistic difference in therapeutical effectiveness among drug combinations utilized. However, the use of amikacin seems to improve infection control when added to the therapy.